The Influences of Fashion as a Soft Power Towards France’s Economic Growth - Riris Parada Elisa Frans; Maria Indira Aryani (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2020)
As time changes, there are various ways to achieve national interests. The focus to gain is no longer only on coercion through military force or economic threat but also could be reached through perspective, culture, or ideology or also known as soft power. France is widely recognized as one of the fashions and luxury country. Indeed, fashion is a part of France’s social and cultural life. The industry of fashion is dominated in France. By this common knowledge, the author starts the research with aims to show the success of France by using fashion as an instrument of soft power and the contribution of the fashion industry towards the country’s economy, specifically economic growth. The author provides an overview of the concepts of soft power and economic growth in this paper, and fashion as a culture in France. The author also includes data as reinforcement of this paper. Therefore, it is easier for readers to get information about soft power, economic growth, fashion, and the relations between those three.